(untitled) (Innovative professional education, 2024)
The priority tasks for the formation of environmental competence of vocational education students have been updated. The experience of organizing ecological educational work in a professional education institution with the aim of forming an ecological culture in students as the social foundation of the transition to sustainable development is highlighted. Successful practices regarding the formation of environmental thinking and culture among students through project activities, participation in eco-events, involvement in public initiatives in the field of energy saving and green technologies are characterized.